Development of novel pseudocapacitive electrodes for fabrication of hybrid supercapacitor and their performance study through machine learning methods for the application in biomedical devices : - Singh,Mahatim (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Bio-medical Engineering